Electrochemical synthesis and corrosion protection properties of poly(o-toluidine) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2005)
Uniform and strongly adherent poly(o-toluidine) (POT) coatings have been synthesized on low carbon steel (LCS) substrates by electrochemical polymerization (ECP) of o-toluidine under cyclic voltammetric conditions from an aqueous sodium tartrate solution. Cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) measurements, and scanning electron microscopy (SEM) were used to characterize these coatings, which indicates that the sodium tartrate is a suitable medium for the ECP of o-toluidine and it occurs without noticeable dissolution of LCS. Corrosion protection properties of the POT coatings were evaluated in aqueous 3% NaCl by the potentiodynamic polarization measurements and CV. The result of the potentiodynamic polarization demonstrates that the POT coating has ability to protect the LCS against corrosion. The corrosion potential was about 334 mV more positive in aqueous 3% NaCl for the POT-coated LCS than that of bare LCS and reduces the corrosion rate of LCS almost by a factor of 50. (c) 2005 Wiley Periodicals, Inc.
Keywords: conducting polymers; Corrosion resistant coatings; cyclic voltarnmetry; Electrochemical polymerization; FT-IR; Poly(o-toluidine); UV-vis spectroscopy

Electrochemical polymerization of o-anisidine on low carbon steel from aqueous salicylate solution: corrosion protection study - Wankhede, M. G.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
The electrochemical polymerization of o-anisidine was carried out on low carbon steel from an aqueous salicylate medium using cyclic voltammetry. The resulting poly(o-anisidine) coatings were uniform and adherent to the steel substrates. These coatings were characterized by cyclic voltammetry, LTV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction measurements and scanning electron microscopy. The ability of the poly(o-anisidine) coatings to protect low carbon steel in an aqueous 3% NaCl was evaluated by the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(o-anisidine) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; low carbon steel; poly(o-anisidine) coatings

Electrochemical synthesis of corrosion protective polyaniline coatings on mild steel from aqueous salicylate medium - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Science and Technology of Advanced Materials, 2006)
Strongly adherent polyaniline coatings were electrochemically synthesized on mild steel from an aqueous salicylate medium. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The extent of the corrosion protection offered by polyaniline coatings to mild steel was investigated in aqueous 3% NaCl solution, 0.01 M Na2SO4 Solution and in aqueous solutions of NaCl + Na2SO4 with different concentrations by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies reveal that the corrosion resistance of the polyaniline-coated mild steel is significantly higher and the corrosion rate is considerably lower than that of uncoated steel. (c) 2006 Published by NIMS and Elsevier Ltd.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; polyaniline coatings mild steel

Synthesis and characterization of corrosion protective poly(2,5-dimethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Applied Surface Science, 2006)
Poly(2,5-dimethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of 2,5-dimethylaniline in aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly (2,5-dimethylaniline) coatings on Cu substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique. The results of the potentiodynamic polarization demonstrate that the poly(2,5-dimethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(2,5-dimethylaniline) coated Cu than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 5-dimethylaniline) coatings; conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Poly(2

Poly(o-ethylaniline) coatings for stainless steel protection - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Progress In Organic Coatings, 2007)
The poly(o-ethylaniline) coatings were electrochemically synthesized on 304-stainless steel by using cyclic voltammetry from an aqueous salicylate medium. Cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethyaniline on 304-stainless steel. The performance of poly(o-ethylaniline) as protective coating against corrosion of 304-stainless steel in aqueous 3% NaCl was evaluated by the open circuit potential measurements, potentiodynamic polarization technique, cyclic potentiodynamic polarization measurements and electrochemical impedance spectroscopy. The results of the potentiodynamic polarization and cyclic potentiodynamic polarization demonstrate that the poly(o-ethylaniline) coating provides excellent protection to both localized and general corrosion of 304-stainless steel. The corrosion potential was about 0.190 V more positive in aqueous 3% NaCl for the poly(o-ethylaniline) coated steel than that of bare steel and reduces the corrosion rate of steel almost by a factor of 20. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings; stainless steel

Synthesis and corrosion protection study of poly(o-ethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Surface & Coatings Technology, 2008)
Poly(o-ethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-ethylaniline in an aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethylaniline to generate strongly adherent and smooth poly(o-ethylaniline) coatings on Cu substrates. The performance of poly(o-ethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies demonstrate that the poly(o-ethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(o-ethylanitine) coated Cu (similar to 15 mu m thick) than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 70. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings

Poly(o-anisidine) coatings on brass: synthesis, characterization and corrosion protection - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Current Applied Physics, 2009)
Poly(o-anisidine) (POA) coatings were synthesized on brass by electrochemical polymerization of o-anisidine in aqueous salicylate solution by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy., Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The corrosion protection aspects of POA coatings on brass in aqueous 3% NaCl solution were investigated by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The potentiodynamic polarization measurements show that the POA coating has ability to protect the brass against corrosion. The corrosion potential was about 0.204 V versus SCE more positive for the POA coated brass than that of uncoated brass and reduces the corrosion rate of brass almost by a factor of 800. The corrosion behavior of the POA coatings was also investigated by EIS through immersion tests performed In aqueous 3% NaCl solution. The evolution of the impedance parameters with the immersion time was studied and the results Show that the POA acts as a protective coating on brass against corrosion in 3% NaCl solution. The water uptake and delamination area were also determined to further support the corrosion protection performance of the POA coating. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: brass; conducting polymers; Corrosion resistant coatings; cyclic voltammetry; Electrochemical impedance spectroscopy; Electrochemical polymerization; poly(o-anisidine)

Synthesis and corrosion protection aspects of poly(o-toluidine)/CdO nanoparticle composite coatings on mild steel - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Journal of Coatings Technology and Research, 2010)
This study examines the possibility of using poly(o-toluidine)/CdO (POT-CdO) nanoparticle composite coating for corrosion protection of mild steel in chloride environment. The POT-CdO nanoparticle composite coating was synthesized on mild steel from aqueous tartrate solution containing CdO-nanoparticles (size similar to 18 nm) by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-Visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction measurements. The corrosion protection aspects of the resulting POT-CdO nanocomposite structure were investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of these investigations reveal that the POT-CdO nanoparticle composite acts as a protective coating on mild steel and reduces the corrosion rate of mild steel almost by factor of 70.
Keywords: CdO; Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Mild steel; Nanocomposites; Poly(o-toluidine)